Analisis Faktor-Faktor yang Mempengaruhi Keputusan Pembelian Beras di Pasar Jambu Dua Kota Bogor - Asrisah Nurindra; Doni Sahat Tua Manalu; Chintya Kenisah Gultom; Revian Alif Maulana; Rohimah Rohimah; Muhammad Rizky Firmansyah Hs Chandra Praja (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Rice is a food commodity that is widely consumed by the Indonesian people. With the presence of branded and unbranded rice in the sale of rice on the market, it is necessary to study consumer behavior so that consumer needs for rice products are in line with expectations. The objectives of this study are; (1) Analyzing the factors that influence consumers in purchasing rice at Jambu Dua Market, (2) Analyzing the Factors that have a significant influence on rice purchases at Jambu Dua Market. The analysis method used is multiple linear regression. The results concluded that; (1) Factors such as age, income, price and distance have an influence on consumer behavior in purchasing rice at Jambu Dua Market in Bogor City, (2) Factors that have a significant influence on consumer behavior in purchasing rice at Jambu Dua Market in Bogor City are age and price.